The effect of academic socializing strategies on collaboration: Empirical evidence from European economics departments - Peter Schneider (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2010)
We present an explorative analysis from qualitative and quantitative data of fourteen European economics departments for the years 2001 to 2003 and investigate how one component of a successful PhD education, which is socializing PhD students into the academic community, should be designed in order to support intercultural collaboration among PhD students. We employ Multi-Value Qualitative Comparative Analysis (MVQCA) to analyze the data. Our results reveal unique patterns of socializing strategies present in economics departments with either high or low intercultural collaboration among PhD students. It turns out that high intercultural collaboration is characterized by two configurations of different socializing strategies. In the first configuration we find that a high number of foreign PhD students in a department sufficiently explains high intercultural collaboration as it is realized in American research universities. In the second configuration we find that a combination of different backgrounds in academic disciplines among PhD students with active support for research visits sufficiently explains high intercultural collaboration. Low intercultural collaboration is characterized by three single strategies: Financing attendance at academic conferences or events about once per year, no active support for research visits and a small number of foreign PhD students. Each condition is sufficient to explain the outcome. The results for high intercultural collaboration are not affected by any of five resource conditions we added as controls. Low intercultural collaboration though was partly co-explained by low amounts of extra time among faculty and low financial resources of the department. The results indicate that high intercultural collaboration is not only supported by a socializing strategy typical for American research universities but can also be achieved by different socializing strategies.
Keywords: 330